MAKNA TANDA VERBAL DAN NONVERBAL PADA IKLAN MINUMAN DI TELEVISI NASIONAL - Desak Putu Eka Pratiwi dan Hugo Warami NFN (Kibas Cenderawasih : Jurnal Ilmiah Kebahasaan dan Kesastraan, 2019)
Advertising is a business which uses language to persuade people to do something or to buy a product. Advertisement uses language as a main tool to describe a reality. In this case, language is used for two purposes. First, it is used as one of the tools to describe a product being advertised.  Second, after the product description is presented, the language is also used to create an image for that product.  In order to create a particular image, the copy writer often uses unusual, stylish, and fresh words. The language of advertisement which is very controversial and bombastic is very interesting to analyze.  The copy writer not only uses verbal signs in delivering the message of the advertisement but also the nonverbal signs. Especially the advertisements on TV which have a very short duration, the verbal signs are combined with the nonverbal signs to achieve a more effective communication.  This research aims at identifying the meaning of verbal and nonverbal signs used in beverage advertisements on TV. Documentation and observation method are applied to obtain the qualitative data.  Theory of semantics by Palmer (2001) and theory of pragmatic by Yule (1996) are used to analyze the meaning of verbal signs of the advertisements.  In addition, the theory of semiotic by Barthes (1998) is used to analyze the meaning of nonverbal signs in the advertisements. The results are presented through formal and informal method.  The results show that the verbal and visual signs in the TV advertisements carried connotative meaning.